2008
DOI: 10.3758/pp.70.3.508
|View full text |Cite
|
Sign up to set email alerts
|

Task coordination between and within sensory modalities: Effects on distraction

Abstract: Load theory predictions for the effects of task coordination between and within sensory modalities (vision and hearing or vision only) on the level of distraction were tested. Response competition effects in a visual flanker task when it was coordinated with an auditory discrimination task (between-modality conditions) or a visual discrimination task (within-modality conditions) were compared with single-task conditions. In the between-modality conditions, response competition effects were greater in the two-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Indeed, according to perceptual load theory [1][2][3], tasks involving high perceptual load can consume most of attentional capacity, leaving little remaining for processing information that is not directly related to the focal task, such as unexpected alarms [4][5][6][7]. In this sense, several researches have shown that attentional resources are shared between vision and hearing [8][9][10][11]. Some authors also postulate that tasks with high cognitive load (e.g., load in working memory) can lead to a reduced openness to additional stimuli such as auditory distractors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, according to perceptual load theory [1][2][3], tasks involving high perceptual load can consume most of attentional capacity, leaving little remaining for processing information that is not directly related to the focal task, such as unexpected alarms [4][5][6][7]. In this sense, several researches have shown that attentional resources are shared between vision and hearing [8][9][10][11]. Some authors also postulate that tasks with high cognitive load (e.g., load in working memory) can lead to a reduced openness to additional stimuli such as auditory distractors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A replication of the load effects with such a design would allow us to rule out any alternative accounts in terms of potential strategy differences in the two conditions of perceptual load. This same approach has been adopted in several previous studies (Brand-D’Abrescia & Lavie, 2007; Cartwright-Finch & Lavie, 2007; Lavie & Cox, 1997; Lavie & Fox, 2000; Theeuwes, Kramer, & Belopolsky, 2004), each successfully ruling out differential strategies as an alternative explanation of the perceptual load effect. Nevertheless, it seemed desirable to establish that such alternative accounts cannot explain the effect of perceptual load on object recognition found here.…”
Section: Methodsmentioning
confidence: 99%
“…There are two explanations why cold-trained individuals tested in hot conditions demonstrated a loss of performance accuracy and consistency when provided with concurrent feedback. First, these individuals now faced a novel task situation in which external feedback, which had been predominantly relied on during training, and intrinsic sensory information, undiminished under hot test conditions, were both present during force specification, resulting in an increased load on executive control (Brand-D'Abrescia & Lavie, 2008) and competition between intrinsic and extrinsic sensory sources for attention (Scheidt, Lillis, & Emerson, 2010;Seizova-Cajic & Azzi, 2010). Alternatively, performance might have declined because cold-trained individuals had learned to use concurrent feedback in a manner that was calibrated specific to the influence of cold on force production mechanisms.…”
Section: Concurrent Visual Feedback Mediates Thermal Dependent Motor mentioning
confidence: 99%